Higher Visceral and Lower Peripheral Adiposity Characterize Fat Distribution and Insulin Resistance in Asian Indian Women with Polycystic Ovary Syndrome in Mauritius - Vinaysing Ramessur; Sadhna Hunma; Noorjehan Joonas; Bibi Nasreen Ramessur; Yves Schutz; Jean-Pierre Montani; Abdul Dulloo (Obesity Facts)
Introduction: There are controversies about whether women with polycystic ovary syndrome (PCOS) show a disproportionately higher visceral adiposity, and its relevance to their higher cardiometabolic risks. We investigated in women of Asian Indian descent in Mauritius, a population inherently prone to abdominal obesity, whether those with PCOS will show a more adverse cardiometabolic risk profile that could be explained by abnormalities in fat distribution. Methods: Young women newly diagnosed with PCOS (n = 25) were compared with a reference control cohort (n = 139) for the following measurements made after an overnight fast: body mass index (BMI), waist circumference (WC), body composition by dual-energy X-ray absorptiometry, and blood pressure and blood assays for glycemic (glucose, HbA1c, and insulin) and lipid (triglycerides and cholesterols) profiles. Results: Women with PCOS showed, on average, higher BMI, WC, fat mass and lean mass (p < 0.01) than controls, but linear regression analyses indicate that for the same BMI (or same WC), the two groups showed no significant differences in fat mass and lean mass. By contrast, linear regression plots indicate that for the same total fat mass, women with PCOS showed higher trunk, android, and visceral fat (p < 0.01); no difference in abdominal subcutaneous fat; and lower peripheral (gynoid or limb) fat (p < 0.05). Furthermore, women with PCOS showed higher fasting plasma insulin, insulin resistance (HOMA-IR) index, and lower insulin sensitivity index (QUICKI) (all p < 0.001), which were completely or markedly abolished after adjusting for visceral fat or central-to-peripheral fat ratios. Conclusion: In Mauritius, young women of Asian Indian descent with PCOS show altered fat distribution characterized by a disproportionately higher visceral (hazardous) adiposity in parallel to lower peripheral (protective) adiposity, which together explain their exacerbated state of hyperinsulinemia and insulin resistance.